Adapting to climate change in the coastal regions of Bangladesh: proposal for the formation of community-based adaptation committees. (2nd January 2017) - Younus, Md Aboul Fazal
ABSTRACT: The paper outlines a concept and proposal for the formation of 'community based adaptation committees' (CBACs) at the micro-level, and it explains how such local committees would act with respect to the existing organisation of disaster management in Bangladesh. It examines how the CBACs would be sustained locally without colliding with the present system of government. The main objective of this is to identify how the CBACs could act independently as per local demands, without any conflict with the existing system, in order to ensure sustainable adaptation in future. To achieve these objectives the author conducted interviews with key informants at both local and national levels, and also conducted eight participatory rapid appraisal sessions at eight coastal communities. The author finds that severe corruption is impeding the existing system of relief and rehabilitation at community levels. The paper emphasises that the government of Bangladesh urgently needs to formulate a national adaptation policy, and that within that policy the concept of CBACs at community level should be prioritised. This would provide the government with guidelines for the use, at community level, of adaptation funds from developed countries in order to reduce future vulnerability in Bangladesh.